1999
DOI: 10.1115/1.2830582
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Strategies and Resulting Part Stiffnesses in Fused Deposition Modeling

Abstract: In the Fused Deposition Modeling (FDM) process, the choice of deposition strategy plays an important role. In this paper, the effects of different deposition paths on this deposition based LM process are investigated. Some variations on the current deposition strategies are also proposed. The stiffness of parts manufactured by the different strategies is experimentally determined. It is then compared with an analytical model developed using laminate analysis. A good conformance of the laminate model to the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 5 publications
1
56
0
Order By: Relevance
“…The right printing strategy and optimum process parameters improve the mechanical properties of the part [6]. The filling strategy affects the strength and stiffness of a part due to the extent of bonding within layer as well as between layers [7,8]. The mechanical properties of the printed part also depend on the bonding strength between the adjacent roads as well as adjacent layers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The right printing strategy and optimum process parameters improve the mechanical properties of the part [6]. The filling strategy affects the strength and stiffness of a part due to the extent of bonding within layer as well as between layers [7,8]. The mechanical properties of the printed part also depend on the bonding strength between the adjacent roads as well as adjacent layers.…”
Section: Introductionmentioning
confidence: 99%
“…The bond formation among the roads is driven by thermal energy of the extruded material [9]. Researchers [2][3][4][5][6][7][8][9][10][11][12][13] discussed the various process parameters of FDM such as raster orientation, air gap, bead width and temperature effect on the mechanical properties of the final fabricated part. The raster angle was observed to have more influence on the mechanical properties than other parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that shorter scan vectors result in stronger parts. In [58] and [59], parts built by the FDM process were studied. The first of these papers compares the strength of parts made with raster and contour paths, and studies the effect of impregnating parts with five different epoxies and composite supplements in differing amounts.…”
Section: Path Planningmentioning
confidence: 99%